The donor problem - Klaus Abbink; Matthew Ellman (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2004)
Donors often rely on local intermediaries to deliver benefits to target beneficiaries. Each selected recipient observes if the intermediary under-delivers to them, so they serve as natural monitors. However, they may withhold complaints when feeling unentitled or grateful to the intermediary for selecting them. Furthermore, the intermediary may distort selection (e.g. by picking richer recipients who feel less entitled) to reduce complaints. We design an experimental game representing the donor's problem. In one treatment, the intermediary selects recipients. In the other, selection is random - as by an uninformed donor. In our data, random selection dominates delegation of the selection task to the intermediary. Selection distortions are similar, but intermediaries embezzle more when they have selection power and (correctly) expect fewer complaints.
Keywords: C90; D63; O12; 330; Development; Entitlement; Experiments; Fairness; Intermediaries; Monitoring; Targeting; Punishment; Spende; Test